PERSEPSI SISWA TENTANG PEMBELAJARAN DARING DAN LURING PADA MATA PELAJARAN GEOGRAFI KELAS XI IPS DI SMA NEGERI 1 TUALANG PROVINSI RIAU - Lusiana, Eva; Suasti, Yurni (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This study aims to analyze the perceptions of students about online learning and offline learning in Geography at SMA Negeri 1 Tualang. This type of research is qualitative, using informants in this study are students of class XI IPS, geography teachers and curriculum representatives at SMA Negeri 1 Tualang. Data collection techniques were collected from interviews and documentation. The results of this study found that students had positive perceptions of offline learning, and negative perceptions of online learning. Students perceive that they want learning activities in Geography to be carried out offline rather than online. This can be seen from the implementation of offline learning which is carried out more effectively than online learning. It is said to be effective because in practice students participate in learning, students understand the material better, and the learning outcomes obtained are better when online